Education and Training in Global Occupational Health and Safety: A Perspective on New Pathways to Sustainable Development. Issue 3 (10th October 2018) - Paganelli, Matteo; Madeo, Egidio; Nabeel, Ismail; Lecca, Luigi Isaia; Pilia, Ilaria; Pili, Sergio; Fostinelli, Jacopo
The institution of specific Occupational Health and Safety (OHS) training programs open to international trainees from developing countries in some European, American and Asian universities is now a well-established reality. Courses and seminars that focus particularly on this subject, widely varying in approach and duration, have been held for years at these universities; these academic institutions have combined their potential to attract students from developing countries with the scheduling of interesting lectures and training activities, depending on the availability of funds sufficient to cover travel and lodging costs. Interdisciplinarity is the key to the entire program and is its main strength, as the trainees have the opportunity to condense the technical notions and methodological aspects of different disciplines (occupational health, industrial hygiene, safety management, ergonomics) in one course. We firmly believe that these programs are a precious instrument for the training of occupational health professionals from low-income countries, as they are able to address their choices correctly, hopefully achieving the goal of reducing the human costs of development.